2007
DOI: 10.1080/00224490701263843
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Woman-Initiated HIV Prevention Methods among Female Sex Workers in Southern China

Abstract: Rapid changes in China over the past two decades have led to significant problems associated with population migration and changing social attitudes, including a growing sex industry and concurrent increases in STIs and HIV. This article reports results of an exploratory study of microbicide acceptability and readiness and current HIV prevention efforts among female sex workers in two rural and one urban town in Hainan and Guangxi Provinces in southern China. The study focused on these women's knowledge and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Of particular note was the interest in the device by women working in the entertainment industry, both because of the ability of the device to provide dual protection and because it was female-initiated. This interest in, and willingness to use, the Woman's Condom by women working in the entertainment industry is consistent with reports of their interest and use of other female condom products 2224…”
Section: Discussionsupporting
confidence: 84%
“…Of particular note was the interest in the device by women working in the entertainment industry, both because of the ability of the device to provide dual protection and because it was female-initiated. This interest in, and willingness to use, the Woman's Condom by women working in the entertainment industry is consistent with reports of their interest and use of other female condom products 2224…”
Section: Discussionsupporting
confidence: 84%
“…Research on microbicides has only recently begun to be conducted in China, 21 and little is known about personal psychological, socioeconomic, and cultural factors affecting acceptance of microbicides and how these factors work in China. More understanding of Chinese women's attitudes toward microbicides and cultural norms about this intravaginal practice is needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, they also reported using several supplements to or substitutes for condoms, some of which are common among other at-risk populations, such as douching (Martino, Youngpairoj, & Vermund, 2004; McKee et al, 2009) and some of which may be unique to Chinese women, such as traditional Chinese medicines (Weeks et al, 2007; Xia & Yang, 2005). The most common prevention methods our study participants reported using in addition to or as replacements for condoms included the following:

Douching and washing themselves after sex and their clients before sex : Products they washed with included feminine hygiene products, soap, water, alcohol, antibiotics, and other medicinal creams.

…”
Section: Resultsmentioning
confidence: 99%
“…Many of these products’ packages include claims of efficacy in preventing HIV and STI. Women also integrated traditional Chinese medicines philosophies into their prevention routines, such as consumption of foods with properties believed to cleanse their bodies or elevate natural immunity (Weeks et al, 2007). …”
Section: Resultsmentioning
confidence: 99%